2013
DOI: 10.12816/0000048
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis among Children at King Hussein Medical Center

Abstract: Objective: Eosinophilic esophagitis is a clincopathologic entity characterized by esophageal symptoms in association with a dense eosinophilic infiltrate, the aim of this study is to describe the clinical presentation, laboratory, endoscopic and histopathologic results in children diagnosed with eosinophilic esophagitis. Methods: This is a retrospective review of the medical records for 38 children with histologic diagnosis of eosinophilic esophagitis performed at King Hussein Medical Center, during the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The majority of the patients were boys. The authors concluded that EoE in Jordan had clinical, endoscopic, and pathological features similar to those described in other countries [12].…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…The majority of the patients were boys. The authors concluded that EoE in Jordan had clinical, endoscopic, and pathological features similar to those described in other countries [12].…”
Section: Introductionmentioning
confidence: 54%
“…Although our study was not a true epidemiological study and there are no previous numbers for comparison, when comparing our numbers (21 cases in 5 years) to the number of diagnosed cases in another referral centre in Jordan with a higher endoscopy service volume [12] (38 cases over 10 years), the incidence may be increasing. EoE is reported more frequently in men than in women.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations